An integrated individual, community, and structural intervention to reduce HIV/STI risks among female sex workers in China - Kang, Dianmin (BioMed Central, 2013)
BACKGROUND: We assessed the effectiveness of an integrated individual, community, and structural intervention to reduce risks of HIV and sexually transmitted infections (STIs) among female sex workers (FSWs). METHODS: The integration individual, community, and structural intervention was implemented from 2004 to 2009 in six counties of Shandong Province. Post-intervention cross-sectional surveys were conducted in six intervention counties and 10 control counties. RESULTS: Of 3326 female sex workers were recruited and analyzed in the post-intervention survey with 1157 from intervention sites and 2169 from control sites. No HIV positive was found in both intervention and control counties. The rate of syphilis was 0.17% for intervention sites and 1.89% for control sites (OR = 11.1, 95% CI: 2.7, 46.1). After adjusted for age, marital status, education, economic condition, recruitment venues, the rates of condom use in the last sex with clients(AOR = 2.7; 95% CI: 1.9, 3.8), with regular sex partners(AOR = 1.5; 95% CI: 1.1, 1.9) and consistent condom use in the last month with clients (AOR = 3.3; 95% CI: 2.6, 4.1) and regular sex partners (AOR = 1.7; 95% CI: 1.3, 2.3) were significantly higher in intervention sites than that in control sites. The proportion of participants correctly answered at least six out of eight HIV-related questions (83.3%) in intervention sites is significant higher than that (21.9%) in control sites (AOR = 24.7; 95% CI: 2.5, 42.7), the five indicators related to HIV-related intervention services ever received in the last year including HIV testing(AOR = 4.9; 95% CI: 2.8, 6.7), STD examination and/or treatment(AOR = 5.1; 95% CI: 4.2, 6.4), free condom(AOR = 20.3; 95% CI: 14.3, 28.9), peer education(AOR = 4.3; 95% CI: 3.5, 5.4), education materials(AOR = 19.8; 95%CI: 13.1, 29.8) were significantly higher in intervention sites than that in control sites, the participants in the intervention sites are more likely to seek medical treatment when they had any disorders (AOR = 3.2; 95% CI: 2.5, 4.2). CONCLUSION: This study found that the integrated individual, community, and structural intervention showed positive impact in reducing HIV and STI risks among FSWs.